2013
DOI: 10.1523/jneurosci.1749-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Central Amygdala GluA1 Facilitates Associative Learning of Opioid Reward

Abstract: GluA1 subunits of AMPA glutamate receptors are implicated in the synaptic plasticity induced by drugs of abuse for behaviors of drug addiction, but GluA1 roles in emotional learning and memories of drug reward in the development of drug addiction remain unclear. In this study of the central nucleus of the amygdala (CeA), which is critical in emotional learning of drug reward, we investigated how adaptive changes in the expression of GluA1 subunits affected the learning process of opioid-induced context–reward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 70 publications
(105 reference statements)
2
28
0
Order By: Relevance
“…Overexpression of GluA1 (Gria1) subunits of AMPA receptors in CeA facilitated the extinction of morphine place preference, whereas downregulation of GluA1 subunits in this same region had the opposite effect (60). In addition, drug seeking behaviors can be attenuated by intra-CeA infusion of agonists of metabotropic glutamate receptors (61), D2/D3 dopaminergic receptors (62), or 5HT-2C serotonergic receptors (63).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of GluA1 (Gria1) subunits of AMPA receptors in CeA facilitated the extinction of morphine place preference, whereas downregulation of GluA1 subunits in this same region had the opposite effect (60). In addition, drug seeking behaviors can be attenuated by intra-CeA infusion of agonists of metabotropic glutamate receptors (61), D2/D3 dopaminergic receptors (62), or 5HT-2C serotonergic receptors (63).…”
Section: Discussionmentioning
confidence: 99%
“…A discussion of opioid function in the amygdala is beyond the scope of this article. There is strong evidence for a critical role of the amygdala, and the CeA in particular, in opioid dependent pain modulation (Manning and Mayer 1995a;Zhang et al 2013;Fields 2000;Manning and Mayer 1995b;Manning 1998) and reward mechanisms (Bie et al 2012;Cai et al 2013), and μ-, κ- and δ-opioid agonists can have direct effects on CeA amygdala neurons (Zhu and Pan 2004;Bie et al 2009). However their role in pain-related amygdala processing and plasticity remain to be determined.…”
Section: Pharmacology Of Pain-related Processing In the Amygdalamentioning
confidence: 99%
“…Finally, we further verified the results of this GluA1 role by knocking down the GluA1 expression in CeA with an AAV vector expressing a short-hairpin interfering RNA against the GluA1-encoding gene Gria1 (AAV-GluA1-shRNA) and a control vector with scrambled shRNA sequence, as we described and validated previously. 41,44 We found that CeA infusion of the AAV-GluA1-shRNA vector for GluA1 knockdown failed to change the preference/aversion behavior under normal conditions; however, the GluA1 knockdown significantly increased the withdrawal-induced CPA behavior ( Figure 5), an effect opposite to that of GluA1 overexpression shown above. These results further support the notion that the activity of GluA1 AMPARs in CeA reduces the aversive effect of opioid withdrawal.…”
Section: Knockdown Of Glua1 In Cea Potentiates Morphine Withdrawal-inmentioning
confidence: 73%
“…The construction and their functional validation of adeno-associated virus (AAV) vectors for GluA1 overexpression (AAV-GluA1) and GluA1 knockdown (AAV-GluA1-shRNA) have been described in our previous studies. 35,41,44 The vector AAV-green fluorescent protein (GFP) was used as control. An animal was injected with 1 ll ($5 Â 10 9 genome copy (GC)/ll) AAV-GluA1 virus, or 1 ll ($2 Â 10 9 GC/ll) AAV-GluA1-shRNA virus into CeA on each side of the brain.…”
Section: Adeno-associated Virus Vectorsmentioning
confidence: 99%